Influence of low birth weight on the developmental outcome of children in the first year of school. - Dharmage, S.C (My University, 1995)
LBW group was found to have a lower level of intellectual performance both at the time of school entry and after six months of schooling. The significant factors that influenced this association were: low socio economic status, low age and lower educational level of the mother, lower duration of pre school education, high level of school absenteeism, lack of availability of reading material, lower nutritional status. The significant influence that LBW had on the scholastic performance after 6 months of school attendance was no longer seen when the performance of the child at the time of school entry was accounted for. Though low birth weight per se was not shown to influence the risk of low height for age, birth weight which is low in relation to the period of gestation was found to be significantly associated. No association was observed between LBW and behavioural problems. These findings highlight the need for special attention for the LBW group, during the pre school period to maximize their intellectual potential and growth